Mechanisms of aggregation in an ant-tended treehopper: Attraction to mutualists is balanced by conspecific competition - Morales, Manuel A. (PLoS One, 2017)
Understanding the spatial structure of populations and communities has been a dominant focus of ecological research, and spatial structure is increasingly seen as critical for understanding population dynamics. Habitat (or host) preference is a proximate mechanism that can generate aggregation or overdispersion, lending insight into the ultimate consequences of observed spatial distributions. Publilia concava is a univoltine phloem-feeding insect that forms mutualistic associations with ants, which consume honeydew and protect treehoppers from predation. Treehopper adults and nymphs are aggregated at the scale of goldenrod plant stems, and previous studies have suggested that this aggregation is an adaptive response that increases feeding performance or maximizes benefits of ant-tending. Previous studies have also shown experimentally that individual treehoppers preferentially oviposit on plants with ants present, but a complimentary hypothesis that treehoppers prefer to oviposit near conspecifics (e.g., to take advantage of density-dependent ant attraction) remains untested. We show that, as expected, the probability of treehopper oviposition increases with ant-presence and relative ant abundance. However, we also find that treehopper oviposition decreases with increasing treehopper density. Thus our results are inconsistent with the hypothesis that treehopper aggregation is a socially cooperative strategy to attract ants; we suggest that aggregation is a form of conflict and an unavoidable by-product of individual responses to ant-tending levels.